Peran Petugas Apron Movement Control (Amc) Dalam Pengawasan Keselamatan Sisi Udara Di Bandar Udara Tambolaka Sumba Barat Daya - Rahimuddin; Oktovianus Bryan Debby Sesa Tukan (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
ABSTRACT, Apron Movement Control (AMC) officers often find Ground Handling officers who do not use ear protection and drive GSE vehicles that exceed the maximum speed of 20 KM, causing the GSE vehicle to suddenly die. This researcher aims 1) To determine the role of Apron Movement Control (AMC) officers. 2) To find out the obstacles for Apron Movement Control (AMC) officers in an effort to improve safety on the air side and to find out solutions in solving the obstacles for Apron Movement Control (AMC) officers. This study uses a qualitative method. The tools used were the researchers themselves, with the results of observations in the Apron Movement Control (AMC) unit, interviews and documents as supporting documents to answer the research questions, the researchers conducted a 3-stage analysis consisting of data reduction, data presentation and drawing conclusions. The results of this study indicate that 1) The role of the Apron Movement Control Unit (AMC) at Tambolaka Airport, Sumba Barat Daya, is located at domestic and international airports which play a very important role in aviation security and safety including providing instructions and supervising all vehicles and personnel traveling serves to oversee the movement of aircraft in the area of ​​aircraft that are currently operating on the Apron and Runway. 2) Obstacles in the Apron Movement Control Unit (AMC) Tambolaka Airport, Southwest Sumba, namely the obstacles experienced when carrying out supervision, there is still a lack of ear protection when monitoring the performance of baggage handling personnel and Apron Movement Control (AMC) officers. naturally the Apron Movement Control (AMC) officer while carrying out surveillance on the apron, the officer found a GSE vehicle that was traveling beyond the maximum limit of 20 km so that it experienced a sudden engine shutdown, not knowing about the rules on the air side.